MANDATORY AUDITOR ROTATION: THE PERCEIVED BENEFITS AND DRAWBACKS (A CASE STUDY IN BPK) - Anggraini, Putri (Jurnal Tata Kelola & Akuntabilitas Keuangan Negara, 2020)
After years of implementation of the policy, there is an inconclusive opinion of whether a mandatory auditor rotation could improve the independence of auditors, including those working within the public sector, such as BPK. This study intends to empirically test the impact of mandatory rotation towards auditors' independence in fact and in appearance. Additionally, the study examines how auditor satisfaction towards the policy affects their perceived benefits and drawbacks of the scheme. Following a statistical assessment of primary data using the independent-samples t-test, findings show that independence in appearance of auditors would be enhanced as a result of mandatory rotation. The rotation policy, however, could not by itself improve auditors? independence in fact. Consequently, complementary schemes are needed to preserve the independence in fact of auditors. Further, auditors who have a favorable view of mandatory rotation would assume that the mechanism offers more advantages than disadvantages. On the other hand, unhappy employees would perceive that mandatory rotation brings more adverse effects than positive ones. The vast majority of respondents also believe that the rotation mechanism is necessary to be implemented in BPK. Lastly, a number of valuable respondent inputs aimed to improve the rotation scheme are elaborated in this study.